MiRNA-1284, a regulator of HMGB1, inhibits cell proliferation and migration in osteosarcoma. Issue 4 (13th July 2018) - Lv, Shuai; Guan, Meng
Abstract : Previous literatures have reported the role of human micro RNA-1284 (hsa-miR-1284, in short miR-1284) in diverse cancers. However, its biological function in osteosarcoma pathogenesis remains unknown. In the present study, we investigated the potential role of miR-1284 in osteosarcoma. Expression of miR-1284 and high mobility group box 1 (HMGB1) were examined in 80 tissues obtained from 40 patients. MiR-1284 level was measured in five osteosarcoma cell lines. Relative luciferase activity and HMGB1 expression were examined in MG-63 and U2OS cells transfected with wild-type or mutant 3′-UTR of HMGB1 in the presence of miR-1284 mimics or miR-NC. Cell viability, colony formation, and cell migration were measured in MG-63, U2OS and hFOB 1.19 cells, which were transfected with miR-1284 mimics or miR-NC. In the rescue experiments, recombinant HMGB1 plasmid was transfected into MG-63 and U2OS cells, and cell viability and migration were determined again. Our results indicated that relative level of miR-1284 was lower in tumor tissues compared with its adjacent tissues and it was found suppressed at lower levels in MG-63 and U2OS cell lines. Expression of HMGB1 is significantly elevated in tumor tissues and negatively correlated with miR-1284 expression. MiR-1284 exerted its function by directly binding to 3′-UTR of HMGB1 and regulates expression of HMGB1. The overexpression of miR-1284 inhibited the cell proliferation and migration, and altered the protein expression of epithelial–mesenchymal transition (EMT)-associated genes (E-cadherin, N-cadherin, Vimentin, and Snail), which was reversed by HMGB1 overexpression. In conclusion, miR-1284 can function as a new regulator to inhibit osteosarcoma cell proliferation and migration by targeting HMGB1.